Cultural functions and dysfunctions of media in Nigeria (2010)
The possible influence of mass media on culture has attracted remarkable scholarly efforts which have understandably left in their trail series of hanging questions. Right from Wright’s influential theorization on the issue of media and culture, researchers have often returned a low score for the media. But studies which have adopted a comprehensive, stakeholders’ approach to the study of media and culture are few. Through a qualitative approach, this study attempted to examine the assessment of Nigerian media as cultural agents by stakeholders—audiences, producers, culture experts and cable vendors. Interviews and focus group discussions showed that the media in Nigeria promote cultural growth as they transmit cultural skills to newer generations and facilitate intra-national cultural contact through intercultural education. As they transmit cultural values, they also indirectly set the standard but the media alone cannot be expected to standardize culture. In their bid to please their audiences so as to be on the good page of the advertiser’s book, the media permit foreign programs thereby permitting cultural invasion. Backed by the advertiser’s money, the audiences have become a rather strong factor in the cultural programming decisions which producers make, and if blames are to be apportioned for cultural dysfunctions, the audiences therefore have a share.